Subalternitas Perempuan Dalam Cerita Pendek Jawa - Wiwien Widyawati Rahayu (Madah: Jurnal Bahasa dan Sastra, 2022)
The placement ofJavanese women as subaltern figures is done through domestication, minority, and discrimination factors. Due to their efforts to escape from this position,  women are often considered to be fighting against the culture that surrounds them.. The construction of the resistance is narrated in five Javanese short stories in  Djaka Lodang, a weekly magazine, which is the source of the data. Therefore, this study aims to determine the forms of subalternity; why the subalternity still exists, what shackles surround it; how  women afford to break free from the shackles; what forms of negotiation women do in social practice; and the reasons of choosing the negotiation. The literature study was carried out by taking an inventory and identifying material objects as data sources, reading the texts heuristically and hermeneutically to classify data based on themes. Then, analyzing data in accordance with subalternity indicators according to Spivak. Finally, this study shows that even though female characters experience subalternity, both by themselves and by others, it does not mean that Javanese women are placed or place themselves as sufferer objects . Self-negotiation with the surrounding culture is an option as a solution to create harmony by not ignoring happiness as an embodiment of equality.